2009
DOI: 10.1055/s-0029-1210708
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of High Parathyroid Hormone Concentration on Calcitonin in Patients with Primary Hyperparathyroidism2)

Abstract: Serum calcitonin (CT), parathyroid hormone (PTH), and calcium levels were measured in 23 patients with primary hyperparathyroidism. PTH was determined by a midregion (M-RIA) and a carboxyl-terminal (C-RIA) specific PTH-RIA. Only 2 patients had elevated CT levels. In contrast to the findings in 46 healthy controls, the CT levels did not correlate with calcium levels. Patients who had the highest iPTH values showed a negative correlation between CT and iPTH (M-RIA (n = 7): R = -1.0000, p less than 0.001; C-RIA (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The relationship between CT and hypercalcemia revealed some discrepancies: if an acute increase of serum calcium was clearly demonstrated to stimulate CT secretion, the effect of chronic hypercalcemia on CT secretion remains unclear [2,6,7,8,9,10,11,12]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The relationship between CT and hypercalcemia revealed some discrepancies: if an acute increase of serum calcium was clearly demonstrated to stimulate CT secretion, the effect of chronic hypercalcemia on CT secretion remains unclear [2,6,7,8,9,10,11,12]. …”
Section: Discussionmentioning
confidence: 99%
“…Although most of the authors found normal CT levels [7,8], others have reported basal elevated CT: in about 50% of cases in a series of 28 patients, and in men only from another series of 55 patients [9,10,11]. However, all these studies were done in a small series of patients and used polyclonal CT radioimmunoassays which are not specific of the mature CT monomer, which should explain the reported high CT levels in these series.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Kübler et al. ( 1987 ), the production of CT from the thyroid gland is stimulated by an increase in the number of active “Osteoclasts”, while an increase in the amount of parathyroid hormone (“Para-thyroid hormone”) decreases the secretion of CT. This process is modeled by the term and natural degradation of CT is modeled by .…”
Section: Mathematical Formulationmentioning
confidence: 99%